Prevalence, Antibiotic Resistance, and Control of Pathogenic Shewanella in Seafoods - Tahirah N. Johnson; Gary P. Richards; Salina Parveen (Journal of Food Protection, 2025)
Some Shewanella spp. have been classified as emerging pathogens and are a concern for food safety. Species such as Shewanella algae and Shewanella putrefaciens are known to cause soft tissue necrosis and invasive infections from marine exposure. Seafood consumption has been linked to Shewanella illnesses, raising concerns about public health risks. Seafood consumption has been on the rise in recent years due to its reported benefits and overall positive health and nutritional perception of consumers. However, an emerging seafood pathogen, Shewanella spp., threatens the safety of these products. This review synthesizes existing data on: (i) the prevalence of potentially pathogenic Shewanella spp. in oysters and seawater from locations around the world, (ii) the antibiotic resistance profiles of isolates from diverse geographic regions, and (iii) processing treatments to reduce Shewanella in seafoods. Findings suggest that Shewanella spp. are widespread in seafood and marine environments. Studies have also shown that over time Shewanella spp. have become more resistant to β-lactam antibiotics such as penicillin, ampicillin, and vancomycin. This growing antibiotic resistance is largely attributed to the overuse and misuse of antibiotics in aquaculture and agriculture, contributing to the emergence of multiple-antibiotic-resistant (MAR) bacteria in seafood. The presence of MAR bacteria limits treatment options in the event of infection by Shewanella and other pathogenic bacteria underscoring the need for better control measures in seafood production to ensure public health safety.